EFFECT OF DIFFERENT REMEDIATION TECHNIQUES AND DOSAGES OF PHOSPHORUS FERTILIZER ON SOIL QUALITY AND KLEKAP PRODUCTION IN ACID SULFATE SOIL AFFECTED AQUACULTURE PONDS - Akhmad Mustafa; Jesmond Sammut (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2007)
Acid sulfate soils (ASS) contain sufficient pyrite which, when oxidised following excavation for brackishwater aquaculture ponds, will generate acid and mobilise toxic metals. Production in affected ponds can be low due to poor growth of shrimp and fish, mass mortalities of stock and low plankton blooms. The resultant low soil pH can also cause poor klekap production due to the retention of phosphorus associated with elevated concentrations of Fe and Al in the pond soils. A series of experiments was conducted to determine the effects of different soil amelioration techniques and dosage of phosphorus (P) on soil and klekap production under laboratory conditions. The treatments consisted of two factors. The first factor tested was different techniques for ASS improvement (non-improvement, improvement through liming and improvement through remediation involving forced oxidation of pyrite, flooding and flushing of oxidation products). The second factor tested was phosphorus dosages, that is, with phosphorus and without phosphorus-based fertilizer. Each treatment had three replications. The experiment showed that liming and remediation had the same effect on several soil variables; they raised the soi pH (pHF, pHFOX, pHKCl) and decreased SPOS, Fe and Al. Remediation of ASS decreased retention of P and increased available-P of soil, whereas liming did not show a significant effect on retention of P and available-P in the doses used for this experiment. The interaction between the different soil improvement techniques and phosphorus fertilising showed a significant effect on klekap production with the highest klekap production of 23.21 mg/cm2 found in remediated soil and with a phosphorus fertiliser dosage of 75 kg/ha.